2011
DOI: 10.1177/1049732311403498
|View full text |Cite
|
Sign up to set email alerts
|

Health in Partnership: Family Nursing Practice for People With Breathing Difficulties

Abstract: Reorienting the focus of health systems to incorporate a multifaceted approach that allows for comprehensive and humane health care is pending. Using the participatory paradigm approach, we describe a study of a partnership-based family nursing practice for people with breathing difficulties. We generated data through nine conversations with eight patients accompanied by a close family member (n = 6) and one wife, 15 conversations between the authors, and through a reflective journal. Narrative data analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(60 citation statements)
references
References 25 publications
0
60
0
Order By: Relevance
“…A central finding demonstrated that the participants experienced feeling safe and comforted . This resonates with Jonsdottir and Ingadottir's () study on a partnership‐based nursing practice, which discovered that a sense of security was a significant component, and urged that further research should focus on this. In our study, this was a generic finding that emerged in all three key themes, and was described in three different ways: as a need, as an experience and as a prerequisite to benefitting from the practice.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…A central finding demonstrated that the participants experienced feeling safe and comforted . This resonates with Jonsdottir and Ingadottir's () study on a partnership‐based nursing practice, which discovered that a sense of security was a significant component, and urged that further research should focus on this. In our study, this was a generic finding that emerged in all three key themes, and was described in three different ways: as a need, as an experience and as a prerequisite to benefitting from the practice.…”
Section: Discussionmentioning
confidence: 79%
“…The nurse was not able to refer patients directly to home care services, but she could to assist patients in “finding their way” in the healthcare system if they wanted to reach out to home care services. The purpose was to ensure a complete course of treatment, help patients to cope with their illness at home, improve self‐management skills in everyday life by increasing patients’ understanding of their condition and collaborate in finding specific strategies for prevention and treatment through a dialogue in line with a partnership as practice approach (Ingadottir & Jonsdottir, ; Jonsdottir & Ingadottir, ).…”
Section: The Studymentioning
confidence: 99%
See 3 more Smart Citations